Mengoptimalkan Pemasaran Digital bagi UMKM: Pendampingan Sayuran Organik pada UMKM AD Hidroponik - Herlina Kusuma Wardhani; Frederik Pradana Deniswara; Agus Hermawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Abstract The service activity for AD Hydroponic MSMEs aims to provide assistance that emphasizes digital marketing for the development of AD Hydroponic MSMEs in Malang Regency, where AD Hydroponics is a business in agriculture, namely organic vegetable plantations. This activity was carried out by a team of assistants and the method of this research was observation and implementation based on an analysis of the situation at AD Hydroponic MSMEs. This service was carried out from October to December 2024. The results of the implementation of this assistance went well, where business actors participated and carried out the directions of the assistance team well. It is hoped that the results of this assistance can improve digital marketing skills and also encourage the growth of the AD Hydroponic business in the future.